Improvement of Physicochemical and Solubility of Dipyridamole by Cocrystallization Technology - Gawade, Ashwini; Kuchekar, Ashwin; Boldhane, Sanjay; Baheti, Akshay (Journal of Drug Delivery and Therapeutics, 2021)
The aim of this study was to develop a pH-independent release formulation of dipyridamole (DP) by the combined use of pH-modifier technology and cocrystal technology tartaric acid (TA) was selected as an appropriate pH-modifier in terms of improving physicochemical properties and dissolution behavior of DP under neutral conditions. Molecular docking method was used to identify the suitable conformer.  Upon optimization of the ratio of TA to DP (molar ratio of 1:1, 1:2 and 1:3) was prepared by a solvent assisted griding method. Scanning electron microscopy images revealed that formation of DP-TA co crystals supported by supported by powder X-ray diffraction and differential scanning calorimetry analyses. Spectroscopic analysis suggested that there might be inter-molecular interaction among DP and TA resulting in pH independent dissolution behavior of drug substance. The study confirmed the selection of proper coformer and exhibited enhanced physicochemical, solubility and stability of the Dipyridamole cocrystals. Hence, based upon results it revealed that cocrystallization helps in improving the physicochemical properties of the API.Keywords: Dipyridamole, Coformer, Molecular docking, Radar chart, solvent assisted griding, Cocrystals